Plasma 25-Hydroxyvitamin D Levels and VDR Gene Expression in Peripheral Blood Mononuclear Cells of Leukemia Patients and Healthy Subjects in Central Kazakhstan - Zhumina, A.G.; Li, K.; Konovalova, A.A.; Li, Y.A.; Ishmuratova, M.Yu; Pogossyan, G.P.; Danilenko, M. (Nutrients, 2020)
Low blood levels of the vitamin D metabolite 25-hydroxyvitamin D [25(OH)D] have been associated with an increased risk and poorer outcomes of various cancers, including hematological malignancies. The Central Kazakhstan area has a relatively high incidence rate of leukemia. However, the relationship between vitamin D status and leukemia or other types of cancer in Kazakhstan has not yet been addressed. Therefore, in this first pilot single-center study conducted in Central Kazakhstan, we compared plasma levels of 25(OH)D and the vitamin D receptor (VDR) gene expression levels in peripheral blood mononuclear cells of patients with leukemia and demographically matching healthy volunteers. The levels of 25(OH)D in patients were found to be significantly lower (10.8 7.0 ng/mL; n = 31) than in healthy subjects (21.6 7.8 ng/mL; n = 34; p < 0.0001). A similar di erence was observed in both younger (<60 years old) and older (>60 years old) participants, though there was no association between 25(OH)D concentration and age within the patient group. In female patients, 25(OH)D levels were significantly lower than in male patients (p = 0.04). No significant seasonal variations of 25(OH)D were observed in either the patient or the control group. VDR gene expression levels appeared to be similar in leukemia patients and healthy subjects, and no correlation between the cellularVDRexpression and plasma 25(OH)D concentrations was observed in either group of participants. We did not observe a significant association of 25(OH)D or VDR levels and overall survival of leukemia patients. This observational study conducted for the first time in Kazakhstan supports previous findings demonstrating reduced blood 25(OH)D levels in cancer (leukemia) patients. Larger studies are required to determine whether low 25(OH)D plasma concentrations represent a risk factor for leukemia development and/or progression.
Keywords: vitamin D; 25(OH)D; vitamin D receptor; leukemia; observational study